A dual-functional chemical sensor for the detection of Cu2+ and Cd2+ based on the photochromic diarylethene. (8th January 2022) - Fan, Tingting; Liu, Fangfang; Fan, Congbin; Pu, Shouzhi
Abstract: A dual-functional sensor DTF-o with a photochromic diarylethene moiety has been designed and synthesized. Its structure was confirmed and analyzed by NMR and MS. The photochromism and fluorescence photoswitching properties of DTF-o were studied in acetonitrile/water (9:1, v/v) solution. DTF-o could selectively recognize Cu 2+ by changing its color from colorless to yellow which was attributed to the metal-to-ligand charge transfer (MLCT) absorption band of metal-ligand cooperation. Meanwhile, DTF-o could also be used to detect Cd 2+ through obvious emission intensity enhancement by inhibition of CN isomerization with chelation enhanced fluorescence (CHEF). Finally, DTF-o was successfully used in practical samples and made into test strips to detect Cu 2+ /Cd 2+ with high accuracy. Graphical abstract: Photochromism, color and fluorescence alteration of DTF-o stimulated by Cu 2+ /Cd 2+ and UV/Vis light. Image 1 Highlights: A new dual-functional sensor DTF-o with the diarylethene moiety was designed and synthesized. DTF-o could be served as a colorimetric sensor for recognition of Cu 2+ and fluorescence sensor for detection of Cd 2+ . DTF-o could be applied in practical samples and made into test paper strips to detect Cu 2+ /Cd 2+ with high accuracy.